Pengaruh Perekaman Diri Berbasis Video dengan dan Tanpa Pengawasan Pelatih terhadap Keterampilan Dasar Tenis Pemula: Mengontrol Efikasi Diri Dasar - Resty Agustryani; Nevitaningrum Nevitaningrum; Melya Nur Herliana; Novi Soraya; Trisnar Adi Prabowo (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. This study examined whether an exercise training model centered on self-recorded practice videos produces greater improvements in beginner tennis players’ fundamental skills than unsupervised free practice, and whether outcomes differ by the presence of online coach monitoring. Accordingly, we compared (1) a monitored self-recording model, (2) an unmonitored self-recording model, and (3) a free-practice control, while controlling for baseline self-efficacy. Materials and methods. An experimental pretest–posttest control group design involved 24 first-semester students (12 male, 12 female) from the Siliwangi University Tennis Club with no formal tennis training. Participants were randomly assigned to: (1) video-based self-recording monitored by a coach via online supervision, (2) video-based self-recording without monitoring, and (3) unsupervised free-practice control. The intervention lasted 12 weeks (3 sessions/week; 36 sessions). This training session lasted 120 minutes, including a 15-minute warm-up, 90 minutes of main training, and a 15-minute cool-down. The intensity of the training was controlled at a low to moderate level (60%–75% of HRmax). Forehand accuracy (FA) and backhand accuracy (BA) were measured using the Dyer Tennis Test, service accuracy (SA) using the Hewitt Tennis Achievement Test, and self-efficacy (SE) using the Endurance Sport Self-Efficacy Scale (ESSES). Paired -tests assessed within-group changes, and MANCOVA tested posttest skill differences while controlling for pretest SE. Results. Only Group 3 showed no significant improvement in BA (p = 0.109); Groups 1 and 2 significantly improved FA, BA, SA, and SE (p < 0.005). Group had a significant multivariate effect on posttest tennis skills after controlling for pretest SE (p < 0.000; ). Pretest SE significantly influenced FA, BA, and SA (p = 0.021; ), predicting posttest FA (p = 0.027) and SA (p = 0.036), but not BA (p = 0.221). Conclusions. Video-based self-recording improves beginner tennis skills and self-efficacy beyond unsupervised free practice. Baseline self-efficacy should be considered in training design because it relates to post-intervention performance, particularly forehand and service accuracy. Future research should involve larger, diverse samples, include retention tests, and explore equipment modifications reported to enhance technical control and self-efficacy in beginners.